The Relationship Between Chinese College Student Offspring's Physical Activity and Father Physical Activity During COVID-19 Pandemic - Zhang, Feng; Liu, Wei; Deng, Lamei; Li, Zhifu; Wang, Yajun; Jin, Bo (Frontiers in Public Health, 2022)
The purpose of this study was to evaluate the relationship between physical activity of Chinese college students and the physical activity of their parents. This relationship was examined by linear regression. The results showed that (1) the physical activities of China's college students will be refurbished and used for the parents. The offspring of COVID-19's later generation sports population showed that the offspring's physical activity was not broken during the later stage of the epidemic, and the coefficient of promotion (r=1.515) (p<0.01) of the offspring's participation in the physical activities was. (2) The important variable that the increase or decrease of the sports population of the parents is affected by their children is occupation. Therefore, it shows the dynamic role of individuals and the two-way nature of socialization in the process of socialization. With the transformation from traditional society to modern society, promoting college student's physical activities can increase parents' physical activities and improve the level of social physical activities.